Regional Autonomy In Literature: Indonesian And International - Achmad, Mansyur (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2020)
The purpose of this study is to determine regional autonomy in Indonesia with comparisons in other countries. The research method used in this research is qualitative by analyzing the literature on 39 previous studies. The results showed that the number of regions in Indonesia is included in a large capacity. The impact of this figure is the need for large and external supervision so that regional autonomy becomes the answer in fulfilling public services to the people in Indonesia. Keywords : Autonomy, Regional and Regional Autonomy